A Behavior-Manipulating Virus Relative as a Source of Adaptive Genes for Drosophila Parasitoids - Di Giovanni, Deborah; Lepetit, David; Guinet, Benjamin; Bennetot, Bastien; Boulesteix, Matthieu; Couté, Yohann; Bouchez, Olivier; Ravallec, Marc; Varaldi, Julien (Molecular biology and evolution, 2020)
Abstract Some species of parasitic wasps have domesticated viral machineries to deliver immunosuppressive factors to their hosts. Up to now, all described cases fall into the Ichneumonoidea superfamily, which only represents around 10% of hymenoptera diversity, raising the question of whether such domestication occurred outside this clade. Furthermore, the biology of the ancestral donor viruses is completely unknown. Since the 1980s, we know that Drosophila parasitoids belonging to the Leptopilina genus, which diverged from the Ichneumonoidea superfamily 225 Ma, do produce immunosuppressive virus-like structure in their reproductive apparatus. However, the viral origin of these structures has been the subject of debate. In this article, we provide genomic and experimental evidence that those structures do derive from an ancestral virus endogenization event. Interestingly, its close relatives induce a behavior manipulation in present-day wasps. Thus, we conclude that virus domestication is more prevalent than previously thought and that behavior manipulation may have been instrumental in the birth of such associations.